Who Does Well in Life? Conscientious Adults Excel in Both Objective and Subjective Success - Duckworth, Angela L.; Weir, David R.; Tsukayama, Eli; Kwok, David (Frontiers in Psychology, 2012)
This article investigates how personality and cognitive ability relate to measures of objective success (income and wealth) and subjective success (life satisfaction, positive affect, and lack of negative affect) in a representative sample of 9,646 American adults. In cross-sectional analyses controlling for demographic covariates, cognitive ability, and other Big Five traits, conscientiousness demonstrated beneficial associations of small-to-medium magnitude with all success outcomes. In contrast, other traits demonstrated stronger, but less consistently beneficial, relations with outcomes in the same models. For instance, emotional stability demonstrated medium-to-large associations with life satisfaction and affect but a weak association with income and no association with wealth. Likewise, extraversion demonstrated medium-to-large associations with positive affect and life satisfaction but small-to-medium associations with wealth and (lack of) negative affect and no association with income. Cognitive ability showed small-to-medium associations with income and wealth but no association with any aspect of subjective success. More agreeable adults were worse off in terms of objective success and life satisfaction, demonstrating small-to-medium inverse associations with those outcomes, but they did not differ from less agreeable adults in positive or negative affect. Likewise, openness to experience demonstrated small-to-medium inverse associations with every success outcome except positive affect, in which more open adults were slightly higher. Notably, in each of the five models predicting objective and subjective success outcomes, individual differences other than conscientiousness explained more variance than did conscientiousness. Thus, the benefits of conscientiousness may be remarkable more for their ubiquity than for their magnitude.